Criminal Policy of Indonesian Criminal Law in Combating the Crime of Phishing - Muhammad Reza Faturahman; Shofriya Qonitatin Abidah; Sonny Saptoajie Wicaksono; Nisrina Khoirunnisa (IPMHI Law Journal, 2025)
Phishing is one of the forms of cybercrime that is increasingly widespread in Indonesia. However, to date, there is no legislation that explicitly defines phishing as an independent criminal offense. On  one hand, this progress offers convenience and efficiency; on the other hand, it gives rise to new challenges that cannot be ignored, one of which is cybercrime. Law enforcement against perpetrators still relies on general provisions in the Indonesian Penal Code (KUHP) and the Electronic Information and Transactions Law Number 1 Of 2024 Concerning The Second Amendment Of Law Number 11 Of 2008 On Information And Electronic Transactions. which are considered insufficient to fully address the complexity of phishing modus operandi. This results in suboptimal prosecution processes and inadequate legal protection for victims. In contrast to Indonesia, the United States has established more specific and comprehensive regulations concerning phishing, supported by integrated law enforcement agencies. Using Lawrence M. Friedman’s legal system theory, it can be concluded that phishing regulations in Indonesia are still ineffective in terms of legal substance, institutional structure, and the public's legal culture. A comprehensive legal reform is needed to appropriately respond to the evolving dynamics of digital crime.